Awal Mula dan Daya Tarik Etnis Tionghoa Datang ke Banjarmasin - Apriza, Rahmat; Handy, Muhammad Rezky Noor; Fathurrahman, Fathurrahman; Yuliantri, Rhoma Dwi Aria (Prabayaksa: Journal of History Education, 2022)
The arrival of an ethnic group in a new area is part of an activity that always occurs at all times. The Chinese ethnicity is one of the foreign ethnicities which is quite easy to find in the Banjarmasin area. Basically, Banjarmasin is part of the Malay and Dayak families. So the arrival of foreign ethnic groups such as the Chinese ethnic in this city is a very interesting topic to discuss. This study aims to trace the initial process of the arrival of the ethnic Chinese and the attraction that made the ethnic group anchor their shipping destinations to this city of a Thousand Rivers. The method used in this study is the historical method which consists of heuristics (source gathering), criticism, interpretation and historiography. Heuristics was carried out by collecting sources or data obtained from interviews with several ethnic Chinese who lived in Banjarmasin and through several written documents regarding the topic of this research. Then proceed with the stage of criticism of sources internally and externally. After going through the criticism stage, an interpretation (interpretation) is carried out in order to process the information from the sources that have been obtained. The final stage is to write (historiography). The research results obtained were that the arrival of ethnic Chinese in Banjarmasin began with shipping and trade activities in the coastal areas of Banjarmasin. The arrival of traders from the Bamboo Curtain country began to develop into a colony which was formed into a village. Banjarmasin itself has an attraction for migrants, namely the wealth of natural resources and the bustling trading port in the coastal area of Banjarmasin Time Formerly. The ethnic Chinese reside and can still be traced to this day and are able to blend in well with the people around them.